Feasibility of fluid responsiveness assessment in patients at risk for increased intracranial pressure - Živković, Aleksandar; Kjaev, Aleko; Schönenberger, Silvia; Krieg, Sandro; Weigand, Markus A.; Neumann, Jan-Oliver (Journal of Clinical Medicine, 2024)
Background: Effective fluid management is important for patients at risk of increased intracranial pressure (ICP). Maintaining constant cerebral perfusion represents a challenge, as both hypovolemia and fluid overload can severely impact patient outcomes. Fluid responsiveness tests, commonly used in critical care settings, are often deemed potentially hazardous for these patients due to the risk of disrupting cerebral perfusion. Methods: This single-center, prospective, clinical observational study enrolled 40 patients at risk for increased ICP, including those with acute brain injury. Informed consent was obtained from each participant or their legal guardians before inclusion. The study focused on the dynamics of ICP and cerebral perfusion pressure (CPP) changes during the Passive Leg Raise Test (PLRT) and the End-Expiratory Occlusion Test (EEOT). Results: The results demonstrated that PLRT and EEOT caused minor and transient increases in ICP, while consistently maintaining stable CPP. EEOT induced significantly lower ICP elevations, making it particularly suitable for use in high-risk situations. Conclusions: PLRT and EEOT can be considered feasible and safe for assessing fluid responsiveness in patients at risk for increased ICP. Notably, EEOT stands out as a preferred method for high-risk patients, offering a dependable strategy for fluid management without compromising cerebral hemodynamics.